Painful stimulation increases spontaneous blink rate in healthy subjects - Paparella, Giulia; Di Stefano, Giulia; Fasolino, Alessandra; Di Pietro, Giuseppe; Colella, Donato; Truini, Andrea; Cruccu, Giorgio; Berardelli, Alfredo; Bologna, Matteo (Scientific reports, 2020)
Spontaneous blink rate is considered a biomarker of central dopaminergic activity. Recent evidence suggests that the central dopaminergic system plays a role in nociception. In the present study, we aimed to investigate whether pain modulates spontaneous blink rate in healthy subjects. We enrolled 15 participants. Spontaneous blink rate was quantified with an optoelectronic system before and after: (1) a painful laser stimulation, and (2) an acoustic startling stimulation. In control experiments, we investigated whether laser stimulation effects depended on stimulation intensity and whether laser stimulation induced any changes in the blink reflex recovery cycle. Finally, we investigated any relationship between spontaneous blink rate modification and pain modulation effect during the cold pressor test. Laser, but not acoustic, stimulation increased spontaneous blink rate. This effect was independent of stimulation intensity and negatively correlated with pain perception. No changes in trigeminal-facial reflex circuit excitability were elicited by laser stimulation. The cold pressor test also induced an increased spontaneous blink rate. Our study provides evidence on the role of dopamine in nociception and suggests that dopaminergic activity may be involved in pain modulation. These findings lay the groundwork for further investigations in patients with pathological conditions characterized by dopaminergic deficit and pain.